Results of challenge of goats with Staphylococcus aureus into the teat of the udder - TZORA, A.; VOIDAROU, C.; KARAMOUTSIOS, A.; SKOUFOS, J. (Journal of the Hellenic Veterinary Medical Society, 2018)
Objective of the present study was to study the outcome of inoculation of Staphylococcus aureus into the teat duct of female goats, which simulates mammary natural infections. In total, 22 lactating goats were used in the study; 8 animals were challenged with a S. aureus strain at a depth of 2 mm into one teat duct (group A), 8 animals were challenged with the same strain at 6 mm into one teat duct (group B) and 6 animals were challenged directly into one gland cistern (group C). Challenge dose was always 1300 cfu. Animals were examined clinically before and after challenge; milk samples were collected for bacteriological and cytological examination, and milk yield measurements were also performed. Goats in group A or B developed a significantly milder response than animals in group C. It is concluded that the evidence indicates a protective role of the normal teat of the udder of goats and that the results also underline the significance of maintaining healthy teats for prevention of mastitis in dairy herds.